Cancer, a disease of aging (part 2) – risk factors for older adult cancer mortality in Switzerland 1991–2008 (Swiss Medical Weekly, 2012)
PRINCIPLES: Cancer is disease of aging that disproportionately affects older adults and often results in considerable public health consequences. This study evaluated gender-age-specific cancer mortality risk factors in older adults in Switzerland with attention to the most common types of cancer. METHODS: The population included all individuals ≥65 years old based on 1990/2000 censuses linked to mortality records through end of 2008. Cancer mortality relative risk was assessed by gender-age-specific all-cancer and cancer-specific mortality hazard ratios (HR) with 95% confidence intervals (CI) from adjusted Cox proportional hazards regression models. RESULTS: The risk profile of dying from cancer was similar in older men and women across most socio-demographic characteristics: higher cancer mortality risk with lower educational attainment (all-cancer men HR = 0.84 [95%CI 0.82, 0.85] tertiary, HR = 1.09 [95%CI 1.07, 1.10] compulsory, women all-cancer HR = 0.95 [95%CI 0.92, 0.98] tertiary, HR = 1.03 [95%CI 1.02, 1.05] compulsory) and unmarried marital status. Cancer mortality risk factors varied less than hypothesised across older age-groups. However, for outcomes and characteristics with age-specific variation the oldest (≥85 years) generally showed the lower cancer mortality relative risk (except for non-Swiss lung cancer risk). CONCLUSION: These comprehensive epidemiological results indicate that in Switzerland (like other developed countries) age alone is not the only important cancer risk factor and risk is not necessarily the same across older age-groups; providing additional needed information about the aging-cancer nexus. However, additional studies especially with consideration of stage of disease, treatments received and comorbidity are needed.